KESIAPAN GURU TERHADAP LITERASI DIGITAL PADA IMPLEMENTASI KURIKULUM MERDEKA DI SD NEGERI SEMBUNGAN - Hujjah Alfiah Suryaningsih; Heru Purnomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2023)
This study aims to analyze teacher readiness for digital literacy in the context of implementing the independent Curriculum in Elementary Schools. The main problem studied is the extent to which elemtary school teacher have adequate knowledge , skills and attitudes in integrating digital technology into the learning process. The research method used was qualitative. Data were obtained through library research and field observations related to the implementation of the Independent Curriculum. The result of the research show that the discussion identified several factors that influence teacher readiness for digital literacy, including a lack of adequate training, limited access to adequate tools and infrastructure, and concerns about the effective use of technology in learning. Indicators in dealing with the readiness of teachers for Digital Literacy in the Independent Curriculum are (a) Critical thinking and problem solving (b) Communication and collaboration (c) Understanding/literacy of Technology and Information Literacy. All of this is so that teachers have the ability to utilize digital media to improve teacher professionalism.